Coal-bed methane migration analysis and numerical model construction of fractured coal body based on multi-field coupling conditions - Zhaoshun Guo; Hui Zhang; Ruibin Yang; Jian Yang; Guangyong Cui; Yong Ma; Yankun Ma (Frontiers in Earth Science)
As an associated resource of coal, coal-bed methane (CBM) has the advantages of high quality and cleanliness, and its development and utilization are of great significance for sustainable development. Deep CBM mining is a multi-field coupling process affected by multiple factors. Therefore, a theoretical and numerical model of fractured coal was established in this paper, and the interaction relationship among the stress of coal, seepage, and diffusion field of gas was explored. Then, the migration laws of coal-bed methane under different circumferential pressure conditions were investigated. The results showed that the stress field of coal affected the diffusion and seepage of CBM by changing the porosity and permeability, and the migration of CBM changed the effective stress and adsorption expansion stress, thus affecting the stress field of coal. Under axial loading, the distribution of Darcy velocity in fractured coal was divided into three regions: fast decrease (in the depth of 0–0.022 m), slow decrease (in the depth of 0.022–0.06 m), and stable stage (more than 0.06 m) from the top boundary to the bottom boundary of the model. With the change of time, the pressure in the three stages decreased from 200 Pa to 0 Pa, and the Darcy velocity decreased from 4.5 × 10−2 m/s to 0 m/s. Along the vertical direction of the model, the Darcy velocity in the fissure and matrix decreased, and the decrease rate of the fissure is faster than that of the matrix. Under a three-dimensional load, the Darcy velocity of the same position shows an approximate linear change with the pressure increase. Finally, based on the difference between the fissure Darcy velocity in uniaxial and three-dimensional conditions, the dominant extraction area of model CBM was determined. The research results can further enrich the theory of gas migration law in coal and improve gas extraction efficiency. Clarifying the principle of gas–solid coupling and increasing the extraction rate will help supplement the supply of clean energy, reduce greenhouse gas emissions, achieve safe coal mine production, and promote environmental protection and sustainable development.